Mauritius : 2008 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Mauritius. (IMF Staff Country Reports; Country Report, 2008)
This 2008 Article IV Consultation highlights that economic growth in Mauritius is responding to structural reform efforts. Tax reform, together with improvements in the business environment and investment initiatives, has spurred foreign investment to unprecedented levels and accelerated growth. The external current account deficit has eased but remains high on investment-driven import growth. The exchange rate appreciated 17 percent in real effective terms in the 12 months ending February 2008 from an overly depreciated level in 2005-06. Mauritius's medium-term outlook has turned more favorable with the effects of the reform effort.